Situation Report: Hungary, 12 June 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dobi on Consequences of Bad Weather on Agriculture Bad Weather Continues Importance of the Remnants of the Private Sector on Agriculture Lajos Feher Leaves for the Soviet Union